Implementation of TOPSIS Method in Determining UKK and UKM Interests Among Students at UIN Bukittinggi - Furqon, Jamaluddin Effendi; Annas, Firdaus; Yuspita, Yulifda Elin; Darmawati, Gusnita (Journal of Computer Science and Informatics Engineering, 2026)
This study is motivated by the declining level of student interest in UKM and UKK organizations on campus over the years. One of the main issues is that many students feel mismatched with the UKK/UKM they selected after joining. Therefore, a decision support system is proposed to address this problem. The objective of this research is to analyze the implementation of a Decision Support System (DSS) using the TOPSIS method in determining students’ preferences for UKK/UKM at UIN Sjech M. Djamil Djambek Bukittinggi. This study applies an applied research approach with TOPSIS as the data analysis method. The evaluation includes accuracy testing between manual calculations and system results, as well as sensitivity testing using the SAW method. The results show that the TOPSIS-based DSS utilizes eight benefit criteria: interest, talent, UKK/UKM description, activity division, activity schedule, recruitment system, membership requirements, and flagship programs. The alternatives include all UKK/UKM at UIN SMDD Bukittinggi. The accuracy test produced a score of 73.23% from 1,188 student data samples, indicating that the system is feasible. Furthermore, the sensitivity test shows a comparison value of 0.13% for SAW and 15.58% for TOPSIS, indicating that TOPSIS is more relevant for this case.